2014
DOI: 10.1056/nejmoa1403108
|View full text |Cite
|
Sign up to set email alerts
|

Initial Therapy with FOLFOXIRI and Bevacizumab for Metastatic Colorectal Cancer

Abstract: FOLFOXIRI plus bevacizumab, as compared with FOLFIRI plus bevacizumab, improved the outcome in patients with metastatic colorectal cancer and increased the incidence of some adverse events. (Funded by the Gruppo Oncologico Nord Ovest and others; ClinicalTrials.gov number, NCT00719797.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
666
2
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 898 publications
(702 citation statements)
references
References 15 publications
21
666
2
13
Order By: Relevance
“…The Hardy-Weinberg equilibrium was evaluated using the χ 2 test [15]. AEs were dichotomized as either mild to moderate (grade 0-2) or severe (grade [3][4]. Association between chemotherapy-associated grade 3-4 AEs and selected genotypes was assessed using the Fisher exact test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Hardy-Weinberg equilibrium was evaluated using the χ 2 test [15]. AEs were dichotomized as either mild to moderate (grade 0-2) or severe (grade [3][4]. Association between chemotherapy-associated grade 3-4 AEs and selected genotypes was assessed using the Fisher exact test.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, triplet chemotherapy with FOLFOXIRI plus bevacizumab gained popularity as conversion strategy in potentially resectable CRC liver metastases [17] or in selected, poor-prognosis patient populations, such as those with BRAF-mutated tumours [18]. However, this strategy of upfront treatment intensification was recently established as a palliative treatment option due to improvement of patients' survival [4]. We demonstrated that oral capecitabine can safely replace 5-FU as the fluoropyrimidine backbone for combination with oxaliplatin and irinotecan (COI regimen) with a manageable toxicity profile [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In diese Studie wurden Patienten mit überwiegend günstigen Risikofaktoren eingeschlossen (1 -4 resektable Lebermetastasen, 52 % 1 Lebermetastase, 26 % 2 Lebermetastasen, 65 % metachrone Metastasierung). Bei primär resektabler Lebermetastasierung wurden eine perioperative Chemotherapie (6 Zyklen FOLFOX4 jeweils vor und nach der Operation) mit der alleinigen Operation [1084] [1110].…”
Section: Hintergrundunclassified
“…As a result of recent advances in treatment, median overall survival (OS) can now be as long as 30 months in selected patient groups. [3][4][5][6] The first-line treatment will be the longest treatment phase and is thus of particular importance regarding the overall treatment strategy. The established standard for many years was continuation of the initial treatment until the occurrence of progression or unacceptable toxicity.…”
Section: Introductionmentioning
confidence: 99%